‘Utārid b. Muhammad al-Hāsib’s “Sirr al-asrār” and his Aphorisms - Parra Pérez, María José (Anaquel de Estudios Árabes, 2009)
‘Utārid b. Muhammad al-Hāsib (fl. 9th –10th c.) was an Eastern astronomer and astrologer who wrote, among other works, a Sirr al- asrār containing astrological and magical materials. The Sirr included a collection of aphorisms, 65 of which are extant in manuscript Escorial 939, fols. 16v-17v. 45 of the aforementioned aphorisms reappear in the Gāyat al-Hakim/ Picatrix, probably written by Maslama b. Qāsim al-Qurtubi (d. 964). This article presents the available information about ‘Utārid and an edition and translation of the aphorisms as they appear in the Escorial manuscript, comparing them to those in the Gāya and in the Latin Alphonsine translation entitled Picatrix.
Keywords: Astrology; Talismanic magic; Aphorisms; Al-Andalus; ‘Utā rid b; Muhammad al-Hā sib; Gā yat al-Hakim; Picatrix; Maslama b; Qā sim al-Qurtubi